Revisiting PIMRS and curriculum instruction management: evaluation of principalship in Banda Aceh - Nurviani, Rahima; Abdullah, Mohammad Ridhuan (Faculty of Education, Universitas Negeri Semarang (UNNES), 2022)
This research explored how Banda Aceh XYZ Schools principals manage the curriculum and instruction and its relatedness to Principal Instructional Management Rating Scale (PIMRS) (Halinger, 1985). This research has 3 research questions and to answer them, a cross-sectional survey, adapted from PIMRS was used and administered to 186 teachers from local schools there. Research findings indicate that Banda Aceh XYZ school principals played moderate roles (µ =3.78) in managing curriculum and instruction, and no statistical difference between male and female teachers’ perceptions of principals’ roles in managing curriculum and instruction. The results pointed to the importance of having workshops and policy discussions to improve teaching and parallel understanding of curriculum and instruction for teachers and administrators.